Konsep Al-Qalb Dan Al-Aql - Aldila Winda Pramita; Uli Ramadhani; Sulaiman Horta Siregar; Yuda Wira; Candra Nugraha Lubis; Ramadan Lubis (CV. ITTC INDONESIA, 2025)
This research aims to analyze the meaning and differences in Islamic theological perspectives, by referring to the text of the Koran. This research uses a library research method which is carried out by reviewing various literature, including previous scientific books and journals that are relevant regarding the concepts of Al-Qalb and Al-Aql. The research results show that a balance between Al-Qalb and Al-Aql is very necessary to achieve harmony in life, both in spiritual, social and intellectual aspects. This concept offers important insight into how both can play a role in forming individuals with noble character and broad insight.